Perception towards Cultured Meat: A Survey of Potential Consumers in India - P S, Girish; Kacham, Santhosh; D C, Praneetha; Rao, Madhusudan; V, Bhaskar; Ramakrishna, C; Raja, Balamanikandan (Journal of Meat Science, 2024)
Meat is an important component of the food basket of India and it plays a critical role in meeting protein demand and ensuring the nutritional security of the ever-growing population. Concerns related to environmental impact, shrinking resources, and animal welfare issues continue to haunt the meat industry. Cultured meat on the other hand promises to produce meat without the need to rear the livestock by utilizing fewer resources with minimum impact on the environment. Here, an effort has been made to capture the perception of Indian consumers towards cultured meat by conducting a survey. Results of the survey revealed that about 60.52% of the respondents are willing to buy the cultured meat if made available. It was found that 45.9% of the respondents who are willing to buy cultured meat are ready to pay a premium price range between 10-30%. Among the respondents, 54.0, 59.1 and 66.5% opinedthat cultured meat is a potential alternative to traditional meat in view of challenges like sustainability, nutritional security, and animal welfare, respectively.